2012
DOI: 10.1021/ac300330g
|View full text |Cite
|
Sign up to set email alerts
|

Selection of DNA Aptamers That Recognize α-Synuclein Oligomers Using a Competitive Screening Method

Abstract: α-Synuclein (α-syn) oligomers are considered major molecules responsible for the onset of Parkinson's disease and dementia with Lewy bodies. α-Syn oligomers thus serve as an important target for the development of drugs and diagnostic tests for neurodegenerative diseases. In this paper we report on the identification of DNA aptamers that bind to soluble α-syn oligomers. A competitive screening method based on aptamer blotting was used for the selection of α-syn oligomer-specific aptamers. This approach resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(163 citation statements)
references
References 32 publications
5
156
2
Order By: Relevance
“…However,t he selection of aptamersf or Ab is difficult, and the target range of nucleic acid aptamers is restricted owing to their low pI. [73,74] Peptides, as an alternative to nucleic acid aptamers for protein binding,c an give ab road target range for protein detection because of their simple chemicals tructure, synthetic accessibility,a nd the greater functional diversity of amino acidsa sc ompared with nucleotides. Li's group reported that Ab 1-42 oligomers could be determined by protein-binding peptidesw ith electrochemical reporters via supermolecule formation ( Figure 8).…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…However,t he selection of aptamersf or Ab is difficult, and the target range of nucleic acid aptamers is restricted owing to their low pI. [73,74] Peptides, as an alternative to nucleic acid aptamers for protein binding,c an give ab road target range for protein detection because of their simple chemicals tructure, synthetic accessibility,a nd the greater functional diversity of amino acidsa sc ompared with nucleotides. Li's group reported that Ab 1-42 oligomers could be determined by protein-binding peptidesw ith electrochemical reporters via supermolecule formation ( Figure 8).…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…Moreover, the reported antibody of Aβ oligomer also recognizes Aβ monomer and other Aβ aggregates and metabolites to some extent. 36 Alternatively, the organic dye-based fluorescence assays (eg, thioflavin T [ThT]) have been commonly used for monitoring the formation of Aβ aggregates in laboratory investigation. 37,38 However, most of the dyes cannot be used to discriminate Aβ oligomer from other β-sheets of Aβ aggregates, 37 thus limiting their applications for the routine test of Aβ oligomer for early diagnosis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…We have used an aptamer previously reported to recognise oligomers and fibrils formed from αS and Aβ21 to enable the sensitive and specific visualisation of protein aggregates at the nanoscale. Aptamers are single‐stranded oligonucleotides developed to have high affinity and specificity and can be made for almost any molecule or structure 22, 23.…”
mentioning
confidence: 99%